Oral Health Status of the Elderly at Tonga, West Region, Cameroon - Yotat Michele Lolita; Agbor Ashu Michael; Ntumba Hubert; Djachechi Florence; Bolenge Jacques (Hindawi Limited, 2015)
Objectives. The aim of this study was to determine the oral health status of elderly persons in Tonga, West Region of Cameroon. Methodology. This is a cross-sectional study of persons of at least 65 years, living in Tonga village, West Region of Cameroon. Results. A total of 183 persons aged between 65 and 94 years, mean age of 73 years ±7 s.d., 83 (45,4%) males, and 100 (54,6%) females participated in the study. The most represented age range was 65-74 years (60.1%); 86 (47.3%) and elders above 65 constituted 1.8% of the total population. More than a third 117 (41.4%) had visible dental plaque, 117 (48,6%) had periodontal pockets >4 mm, 153 (54,1%) had teeth with total crown destruction, 70 (38.3%) had not lost a tooth, 23 (12.6%) had lost 1 tooth, 19 (10.4%) have lost at least 2 teeth, 100 (55.7%) were partially edentulous at the maxilla and 98 (53.6%) at the mandible, 2 (1.1%) were completely edentulous at the maxilla and 3 (1.6%) at the mandible, and 3.8% had removable dentures. The mean DMF index was 6.11 and 69.4% had dental caries. Risk factors to dental caries were toothbrushing and tobacco consumption while dental plaque was associated to pocket depth of 4-6 mm. Barriers to oral health care included ignorance 47 (25.7%), financial difficulties 124 (67.8%), and distance to the nearest clinic 12 (6.5%). Conclusion. The oral status of the elderly was generally poor.